A Thematic Study of the Works of Art of Selected Humorists in the 21st Century - Choudhry, Rifat (sourcecoder, 2024)
This paper conducts a thematic analysis of the works of art of prominent humorists in the 21st century, exploring the underlying themes and messages that permeate their creative output. Through a close reading of selected texts, images, and performances, this study reveals the ways in which contemporary humorists use humor to comment on pressing social issues, challenge cultural norms, and reflect the anxieties and absurdities of modern life. By examining the shared themes and techniques employed by these humorists, this research provides insight into the role of humor in shaping our understanding of the world and ourselves, and highlights the significance of humor as a means of social critique and personal expression in the 21st century.